Quality assessment of groundwater and agricultural soil in Hail region, Saudi Arabia - Amaal M. Abdel-Satar; Manal H. Al-Khabbas; Waed R. Alahmad; Wafaa M. Yousef; Rani H. Alsomadi; Tasneem Iqbal (Egyptian Journal of Aquatic Research, 2017)
Groundwater is highly important in Saudi Arabia as it is extensively utilized for drinking, domestic, agricultural and industrial uses. The aim of this research is to assess the quality of groundwater and agricultural soil in Hail region. The abundance of main cations in ground water was generally in the order K+ < Mg2+ < Na+ < Ca2+, while the order of the anions was Cl− > SO42− > HCO3−. With respect to TDS, Cl−, SO42−, Na+, Ca2+ concentrations, more than 33% of groundwater samples exceeded the allowable levels cited for drinking water, while about 43% of water samples contained Pb levels higher than the drinking water guidelines. Assessment of groundwater’s quality for irrigation was achieved using several indices as sodium adsorption ratio, Na% and residual sodium carbonate. Among these, the majority of index results implied that about 97% of the groundwater samples fall within the excellent category. The total metal concentrations in soil samples were ordered as follows: Cd < Pb ≈ Ni ≈ Cu < Cr < Zn < Mn < Fe. According to soil quality guidelines, there is a slight risk from Ni and Zn and a considerable risk from Cd. The geoaccumulation, single pollution, Nemerow pollution indices showed that the Cd pollution intensity was significant for agricultural soils.